Human rights trade-offs in a context of systemic unfreedom: The case of the smelter town of La Oroya, Peru - Areli Valencia (University of Bath, Centre for Development Studies (CDS), 2012)
This paper examines the interconnecting causes that have placed residents of the community of La Oroya, in Peru's central Andes, in the dilemma of having to sacrifice their human right to health in order to preserve job opportunities at the town's smelter. Using the lens of a 'capability-oriented model of human rights', the paper shows how a constellation of environmental, social, institutional and personal factors have resulted in structuring a context of systemic unfreedom in La Oroya. This is a context in which human rights abuses reproduce systemically, affecting the overall wellbeing of individuals and communities, and in turn, diminishing their ability to transform their reality of unfreedom. The paper argues that to understand fully why some residents of the La Oroya community acquiesced in forfeiting their own rights, particular attention has to be paid to the pernicious manner in which living under unfreedom has historically trapped individuals of this community in a vicious cycle of disadvantage.
Keywords: 330; human rights; extractive industry; capability approach; structural injustice; environment